Democratic responsibility : the politics of many hands in America - Hanagan, Nora, 1981- (University of Notre Dame Press, 2019)
"American society is often described as one that celebrates self-reliance and personal responsibility. However, abolitionists, progressive reformers, civil rights activists, and numerous others often held their fellow citizens responsible for shared problems such as economic exploitation and white supremacy. Moreover, they viewed recognizing and responding to shared problems as essential to achieving democratic ideals. In Democratic Responsibility, Nora Hanagan examines American thinkers and activists who offered an alternative to individualistic conceptions of responsibility and puts them in dialogue with contemporary philosophers who write about shared responsibility. Drawing on the political theory and practice of Henry David Thoreau, Jane Addams, Martin Luther King Jr., and Audre Lorde, Hanagan develops a distinctly democratic approach to shared responsibility. Cooperative democracy is especially relevant in an age of globalization and hyperconnectivity, where societies are continually threatened with harms--such as climate change, global sweatshop labor, and structural racism--that result from the combined interactions of multiple individuals and institutions, and which therefore cannot be resolved without collective action. Democratic Responsibility offers insight into how political actors might confront seemingly intractable problems, and challenges conventional understandings of what commitment to democratic ideals entails. This book will be of interest to scholars and students of political science, especially those who look to the history of political thought for resources that might promote social justice in the present"--